2020
DOI: 10.1002/ppp3.10084
|View full text |Cite
|
Sign up to set email alerts
|

Enset‐based agricultural systems in Ethiopia: A systematic review of production trends, agronomy, processing and the wider food security applications of a neglected banana relative

Abstract: Enset is a staple food for over 20 million people via its starch-rich corm and pseudostem, yet it is virtually unknown outside a narrow zone of cultivation in southern Ethiopia. Due to acculturation and urbanization coupled with climate change, emerging pests and the introduction of new crops, the extensive indigenous knowledge associated with this crop is in danger of being lost, imperilling the future food security and prosperity of millions of Ethiopians. Here, we synthesize the current state of enset ethno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 54 publications
4
84
0
Order By: Relevance
“…For example, enset ensured greater food security for millions of people in Ethiopia's Southern highlands during the famines of the 1970s and 1980s (Brandt et al, 1997). But, enset stands are sometimes being harvested earlier than the full 4-11 year cycle, thereby depleting stands before they mature (Borrell et al, 2020). Thus, while the harvest of stored calories in enset trunks and corms can mitigate food shortages for a time (Brandt et al, 1997), the depletion of enset stands or their loss due to other reasons reduces their subsequent ability to mitigate further disruptions in the food supply and they take longer to recover (Quinlan et al, 2015).…”
Section: Perenniality and Growth Formmentioning
confidence: 99%
“…For example, enset ensured greater food security for millions of people in Ethiopia's Southern highlands during the famines of the 1970s and 1980s (Brandt et al, 1997). But, enset stands are sometimes being harvested earlier than the full 4-11 year cycle, thereby depleting stands before they mature (Borrell et al, 2020). Thus, while the harvest of stored calories in enset trunks and corms can mitigate food shortages for a time (Brandt et al, 1997), the depletion of enset stands or their loss due to other reasons reduces their subsequent ability to mitigate further disruptions in the food supply and they take longer to recover (Quinlan et al, 2015).…”
Section: Perenniality and Growth Formmentioning
confidence: 99%
“…Chessman) is a perennial and monocarpic herb belonging to the banana family and originated in Ethiopia (Vavilov, 1951). Enset is a wonder food and income security crop for more than 20 million people, cultivated by millionof smallholder farmers in south, central and southwestern Ethiopia (Borrell et al, 2020). It is a source of food, cash, animal feed, medicine, fuelwood, construction, and ornament for smallholder farmers in Ethiopia (Jacobsen et al, 2018;Jones, 2000;Zerihun Yemataw et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is widely distributed and presently found in almost all enset growing regions (Welde-Michael et al, 2010;Zerfu et al, 2018). Currently, it is reported that up to 80% of enset farms in enset growing areas of Ethiopia are infected by EXW, which directly affects the livelihood of more than 20 million enset farmers in the country (Borrell et al, 2020:Z. Yemataw et al, 2017. This leads to food insecurity among the rural community.…”
Section: Introductionmentioning
confidence: 99%
“…Enset is an indigenous and herbaceous monocot plant and widely grown as a food crop (James S et al, 2020;Uloro & Mengel, 2014) and it is banana-like perennial plant that the enlarged pseudo-stem and underground corm (carbohydrates) of the plant is used for human consumption (Michael , 2002) and it is called "a national commodity" of Ethiopia (Anita, et al, 1996).…”
Section: Introductionmentioning
confidence: 99%